Single Phase Bidirectional Charger for Electric Vehicles to Support Reactive Power Compensation to Grid - Manwani, Neeraj (Thapar University, 2017)
This dissertation presents a single phase bidirectional plug-in electric vehicle (PEV) charger. The charger proposed here controls the charging rate of the battery and aditionally provides reactive power support to the grid. The battery charger circuit consist of two converters i.e ac-dc boost converter (120V ac to 400V dc) and the dc-dc buck converter. A seperate controller is used for each converter i.e Controller-1 (C-1) and Controller-2 (C-2). C-1 is for ac-dc boost converter and C-2 is for the dc-dc buck converter. The C-1 is used to support the reactive power to the grid to maintain the Power Factor (pf) and voltage regulation. However, the control action of C-1 is done through the dc-link capacitor. The change in controllable commands (P-Q commands) adjust the parameters of the dc side. Whereas C-2 has been designed to control the charging rate of the battery. The battery charging current can vary as per the status of grid. The P-Q commands are the reference active power and reactive power commands given by the user at the input side. In this dissertation, the proposed charger is used to charge the plug-in electric vehicle battery in different charging modes. This dissertation proposes a simulation model and mathematical analysis of the charger. The comparison of the improved results concludes the successful implementation of charger.
Master of Engineering -Power Electronics & Drives
Keywords: Boost rectifier; Controller; Electric vehicle; Reactive power compensation